2016
DOI: 10.6018/analesps.33.1.235351
|View full text |Cite
|
Sign up to set email alerts
|

Women Occupying Management Positions in Top-Level Sport Organizations: A Self-Determination Perspective

Abstract: Título: Mujeres que ocupan cargos de gestión en organizaciones deportivas de primer nivel: una perspectiva desde la autodeterminación. Resumen: Bajo el marco teórico de la Teoría de la Autodeterminación (SDT), el propósito del presente estudio fue investigar si el entorno laboral de mujeres que ocupaban cargos directivos en el deporte era de satisfacción o frustración de las necesidades psicológicas básicas (BPN), y explorar sus motivaciones en estas posiciones. Se realizaron entrevistas semiestructuradas a oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…Although this theme affects male leaders, the fact that it is pervasive among female leaders, as also found by previous research (Pfister & Radtke, 2009), here seen in both contexts, is worrying, especially due to perceived loneliness, vulnerability, shock reactions, lack of sleep, and weight loss. Similar to earlier research (Perez-Rivases et al, 2017), these reactions seem to be worsened by the experience of being blocked and diminished in the leader role. Being exposed to bad work relations as a leader coupled with tense organisational situations is a severe stress problem, or not to say, a mental health issue.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although this theme affects male leaders, the fact that it is pervasive among female leaders, as also found by previous research (Pfister & Radtke, 2009), here seen in both contexts, is worrying, especially due to perceived loneliness, vulnerability, shock reactions, lack of sleep, and weight loss. Similar to earlier research (Perez-Rivases et al, 2017), these reactions seem to be worsened by the experience of being blocked and diminished in the leader role. Being exposed to bad work relations as a leader coupled with tense organisational situations is a severe stress problem, or not to say, a mental health issue.…”
Section: Discussionsupporting
confidence: 78%
“…Other demanding conditions are conflicts and power struggles. In particular, high-level female leaders can suffer considerably from such conditions and be hindered in access and career advancement sometimes by adverse reactions from male colleagues (Pfister & Radtke, 2009) and being ignored, discriminated and combated against their organisational change initiatives (Perez-Rivases et al, 2017). As Adriaanse (2019) expresses, in the long run, this lack of gender equality in leadership can prevent the organization from utilizing its potential to the fullest.…”
mentioning
confidence: 99%
“…According to our results, to feel loved, valued, and connected with significant others in a passionate activity influences the quality of the cognitive process. In this sense, the importance of relatedness satisfaction as a strong predictor of positive intrapersonal outcomes (i.e., positive affect or subjective vitality) has been stated in past research (Alcaraz et al, 2015;Perez-Rivases et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Strong interpersonal relationships with supervisors or mentors and access to professional development activities have been found to aid in the career development of senior-level female administrators (Hancock and Hums, 2016). The working environment can also have an impact on overall motivations and job satisfaction of female sport managers (Perez-Rivases et al, 2017). In their study of female sales managers' experiences across professional sport organizations, Sattler et al (2018) found just over half (61.4%) of female sales managers could identify a workplace mentor, and of that, less than a third (29.7%) identified having another woman as their mentor.…”
Section: The Importance Of Ticket Sales In Marketingmentioning
confidence: 99%